Police-public relationship in security management in Kasarani administrative division, Nairobi county, Kenya. - Mugo Emily Nyawira (Nairobi : Maryknoll Institute of African Studies, 2018)
A research thesis submitted in partial fulfillment of the award of the degree of Masters of Arts in African Studies of Maryknoll institute of African studies of Saint Mary's university Winoma, Minnesota USA and Tangaza college, Nairobi.
Keywords: Research -- Thesis; Police -- public relations -- Kenya; police administration